2022
DOI: 10.1007/s10151-022-02580-6
|View full text |Cite
|
Sign up to set email alerts
|

Overall readmissions and readmissions related to dehydration after creation of an ileostomy: a systematic review and meta-analysis

Abstract: Background Hospital readmissions after creation of an ileostomy are common and come with a high clinical and financial burden. The aim of this review with pooled analysis was to determine the incidence of dehydration-related and all-cause readmissions after formation of an ileostomy, and the associated costs. Methods A systematic literature search was conducted for studies reporting on dehydration-related and overall readmission rates after formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Our study aims to fill this gap in the literature, and the collaborative nature of this multicentre study, will allow capturing real-world data on the current use of stomas in patients with CD and on the complications related to the stoma formation and reversal. One in five patients are readmitted with a stoma-related complication within 30 days of the creation of an ileostomy, with dehydration being the leading cause, occurring in 6% of patients [ 16 ]. The rate of stoma-related complications will likely be higher during the 18-months follow-up of our study, reflecting the high health care cost for a potentially avoidable cause, including long-term complications, which often require further surgery or contribute to mortality [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study aims to fill this gap in the literature, and the collaborative nature of this multicentre study, will allow capturing real-world data on the current use of stomas in patients with CD and on the complications related to the stoma formation and reversal. One in five patients are readmitted with a stoma-related complication within 30 days of the creation of an ileostomy, with dehydration being the leading cause, occurring in 6% of patients [ 16 ]. The rate of stoma-related complications will likely be higher during the 18-months follow-up of our study, reflecting the high health care cost for a potentially avoidable cause, including long-term complications, which often require further surgery or contribute to mortality [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration has been shown to be a cause of readmission in 9.3%-43% of the patients after ileostomy creation without preventive protocols[ 33 - 35 ]. The most recent meta-analysis showed that the pooled incidence of readmission due to dehydration was 6% regardless of HOS prevention and was accompanied by increased medical costs[ 36 ]. Moreover, HOS results in electrolyte imbalance and acute kidney injury in the early postoperative period and may lead to malnutrition and chronic renal impairment in the long term[ 30 , 37 ].…”
Section: Secretory Complication (High Output)mentioning
confidence: 99%
“…The majority of previous reports have defined using specific values of output volume with a timeframe, such as 2000 mL per day[ 38 , 44 , 45 ], 1500 mL per day for two days[ 41 ], 1000 mL per day for three days[ 42 , 46 ], and 2000 mL per day for three days[ 29 , 43 ]. Some authors have used a combination of output volume with laboratory findings of renal impairment and/or physical signs of dehydration[ 36 , 47 ].…”
Section: Secretory Complication (High Output)mentioning
confidence: 99%
“…A 2022 meta‐analysis showed that one in five patients were readmitted with a stoma‐related complication within 30 days of ileostomy creation. Dehydration from high stomal output was the most frequent complication, occurring in 6% of patients and resulting in additional costs of $2750 to $5924 per patient 6 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the time between stoma creation and closure can be considerable, 6 increasing the risk of additional complications, including stomal outlet and peristomal skin irritation issues. A 2016 study showed a more than 8‐month mean interval between LAR and DI reversal, with a further 17% morbidity rate following DI reversal 7 .…”
Section: Introductionmentioning
confidence: 99%